Bahasa Inggris - M. Miftach Fakhri; Della Fadhilatunisa; Yuanita B; Nur Rahmah Sari; Rosidah (Universitas Islam Negeri Alauddin Makassar, 2022)
A good accountant is the one who is able to do the preparation of financial statements. In addition, akuntan must gain an understanding of the financial reporting framework and significant accounting policies intended for use in the preparation of financial statements. Optimization of the preparation of financial statements that have been described above can be further realized by using software in the preparation of financial statements. One application or software that can be used in the preparation of financial statements is